Evaluation of the effectiveness of V-Y plasty of frozen Achilles tendon rupture, with immediate follow-up weight-bearing and rehabilitation. Case analysis - Kacprzak, Bartłomiej; Kisielewska, Anita; Miler, Adrian; Hagner-Derengowska, Magdalena; Kitschke, Ewa; Zukow, Walery (Journal of Education, Health and Sport, 2024)
The Achilles tendon is a strong tendon in the human body but is prone to rupture, especially during recreational activities. Misdiagnosis of ruptures can lead to chronic issues, affecting the quality of life. Surgical V-Y plasty is a technique used to treat chronic Achilles tendon ruptures by lengthening the tendon and restoring its continuity. Two cases of Achilles tendon ruptures were presented, where V-Y plasty was performed along with immediate weight-bearing and rehabilitation. The patients showed significant improvement post-surgery, with no symptoms or restrictions on physical activity after about 6 months. The rehabilitation protocol included functional training, regenerative treatments, and follow-up visits to monitor progress. Studies have shown that surgical treatment is more effective in preventing re-tears compared to conservative treatment for Achilles tendon ruptures. V-Y plasty has been proven to be an effective technique for treating chronic ruptures with large defects in tendon continuity. Immediate weight-bearing and rehabilitation post-surgery have shown positive outcomes in patient recovery. Further research is needed to establish a standardized rehabilitation protocol for Achilles tendon ruptures. The unique management regimen used in the cases presented yielded successful results, emphasizing the importance of immediate rehabilitation post-surgery for improved patient outcomes. V-Y plasty with immediate weight-bearing and rehabilitation is a promising method for treating chronic Achilles tendon ruptures.